From Sociological Interpretation to Political Science. (March 2018) - Barrientos Del Monte, Fernando
From the end of the nineteenth century until well into the 1980s, one spoke of the "political sciences" (in the plural), a concept that included all the disciplines that analyzed political phenomena. "Sociological interpretation" began in the 1960s as a model of social science meant to provide both criticism and direction regarding development policies. Rodolfo Stavenhagen's 1965 "Seven Erroneous Theses about Latin America" is an example of the role played by the political sciences at the time. Given the development of contemporary political science, which seeks dependent and independent variables and mid-range theories and bases its claims on empirical information, the question arises what Latin American political science can (re) learn from the interpretive model employed 50 years ago. Desde finales del siglo XIX y todavía en los años ochenta del siglo XX se hablaba de "ciencias políticas" (en plural), concepto en el cual se incluían todas aquellas disciplinas que analizaban los fenómenos políticos. La "interpretación sociológica" se erigió en la década de los años sesenta como un modelo de ciencia social que formulaba críticas pero también orientaba políticas de desarrollo. "Siete tesis equivocadas sobre América Latina" (1965) de Rodolfo Stavenhagen es un ejemplo del ejercicio de las ciencias políticas de la época. A la luz del desarrollo de la ciencia política contemporánea, que busca variables dependientes e independientes y teorías de alcance medio y funda sus afirmaciones a partir de información empírica, se trata de responder a la pregunta qué puede (re)aprender la ciencia política latinoamericana del modelo interpretativo de hace cincuenta años.